A Comprehensive Experimental Study on Bi-Adhesive Technique Applied to Structural T-Joints - Carvalho, P. M. D.; Campilho, R. D. S. G.; Sanchez-Arce, I. J.; Rocha, R. J. B.; Soares, A. R. F. (Techniques and Innovation in Engineering Research Vol. 1, 2022)
T-joints are used in many applications such as automotive, marine, and aerospace industries. In this work, the bi-adhesive technique is studied, consisting of using two adhesives, placing a more flexible adhesive at the overlap ends and a stiffer one in the central area. To test this method in T-joints, different adhesive ratios were evaluated. To evaluate this concept, a numerical study was carried out using the CZM technique, in the ABAQUS® software, including a study of failure modes, stresses, strength or maximum load (Pm) and dissipated energy (U). The CZM technique was initially validated with experimental results using the current work. The numerical work that followed demonstrated that the strength of T-joints is significantly dependent on the adhesive combination used and that it is possible to achieve increases in Pm and U when compared to single-adhesive joints.